(untitled) (Altre Modernità, 2025)
Among the issues raised by the concept of ‘repertoire’ in literary theory, the most interesting concern its constitution and its dynamics. This paper aims to investigate the effects of the repertoire as cultural memory in a diverse textual corpus unified by the occurrence of the same thematic constellation. The underlying hypothesis is that the presence of very particular thematic elements in several basically independent texts can be derived not so much from direct contact, nor even less from the polygenetic emergence of metahistorical universals, but rather from the subterranean influence of canonical texts of the Western tradition, crystallising in a kind of ‘cultural engram’. This kind of influence determines a transtextual relation in addition to the five categories identified by G. Genette, which I would propose to label ‘cryptotextual relation’. In all the texts investigated in this article, the thematic constellation relating the judicial investigation to patricide and leading to the discovery of a truth contrary to previous assumptions ostensibly implies the ‘cryptotextual’ model of Sophocles’ Oedipus Rex.